Evaluation of flow-induced vibration suppression performances of magneto-rheological damping pipe clamp using PID algorithm. (July 2023) - Hong, Ruidong; Nie, Songlin; Ji, Hui; Nie, Shuang; Gong, Fei
In order to suppress the low-frequency flow-induced vibration of fluid conveying pipeline, this paper develops a magnetorheological damping (MRD) pipe clamp due to its simple structure and strong dynamic adjustability. The mechanical dynamic model of MRD pipe clamp is established, and the vibration control algorithm based on PID is simulated. Comparison analysis on the vibration damping performance of the MRD pipe clamp under uncontrol, passive control, and PID control are conducted. The damping performances of MRD pipe clamp are tested under uncontrol, passive control, and PID control algorithm. The experiment results exhibited that the attenuation rate of each axial displacement and acceleration of pipe system using PID algorithm were more than 80% under sinusoidal excitation force of 600 N and excitation frequency of 2.5 Hz. The experiment results have verified the correctness of the simulation analysis in terms of value and trend. This research will provide the guide for the design and engineering application of MRD pipe clamp system.